2021
DOI: 10.1080/19490976.2021.1926841
|View full text |Cite
|
Sign up to set email alerts
|

Impact of type 1 diabetes on the composition and functional potential of gut microbiome in children and adolescents: possible mechanisms, current knowledge, and challenges

Abstract: Diabetes prevalence and incidence among youth have been increasing globally. Type 1 Diabetes (T1D) in children or adolescents accounts for 5-10% of all diagnosed cases of diabetes. Emerging evidence indicates that genetic factors, especially genes in the human leukocyte antigen region, are not the only factors involved in the predisposition of an individual to T1D. The pathogenesis and development of T1D is driven by both genetic predisposition and environmental factors. Studies indicate that gut microbiota is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(31 citation statements)
references
References 77 publications
(265 reference statements)
1
30
0
Order By: Relevance
“…Positive IA-association was found with 312 out of 327 MAGs in Bacteroides uniformis , 41 out of 43 MAGs in Bacteroides cellulosilyticus , all 11 MAGs in Bacteroides intestinalis , 31 out of 44 MAGs in Bacteroides stercoris and 18 out of 170 MAGs in Bacteroides ovatus . Elevated abundances of the Bacteroides genus, including Bacteroides uniformis and Bacteroides ovatus at the species level, have been reported in seroconverted and T1D subjects 8 , 27 , 28 Findings of elevated abundance of Bacteroides cellulosilyticus , Bacteroides intestinalis and Bacteroides stercoris have been reported in T1D patients 29 Our analysis of MAGs confirmed the positive and consistent signal of IA-association with Bacteroides uniformis, Bacteroides cellulosilyticus , Bacteroides intestinalis , Bacteroides stercoris , and Bacteroides ovatus .…”
Section: Resultssupporting
confidence: 79%
“…Positive IA-association was found with 312 out of 327 MAGs in Bacteroides uniformis , 41 out of 43 MAGs in Bacteroides cellulosilyticus , all 11 MAGs in Bacteroides intestinalis , 31 out of 44 MAGs in Bacteroides stercoris and 18 out of 170 MAGs in Bacteroides ovatus . Elevated abundances of the Bacteroides genus, including Bacteroides uniformis and Bacteroides ovatus at the species level, have been reported in seroconverted and T1D subjects 8 , 27 , 28 Findings of elevated abundance of Bacteroides cellulosilyticus , Bacteroides intestinalis and Bacteroides stercoris have been reported in T1D patients 29 Our analysis of MAGs confirmed the positive and consistent signal of IA-association with Bacteroides uniformis, Bacteroides cellulosilyticus , Bacteroides intestinalis , Bacteroides stercoris , and Bacteroides ovatus .…”
Section: Resultssupporting
confidence: 79%
“…The human gastrointestinal tract houses a vast and diverse intestinal microflora that provides nutrients and intrinsic immunity, regulates epithelial cell growth, and fundamentally affects human health and disease [5]. We have previously confirmed that intestinal I/R induces significant intestinal flora disorders and indicated that intestinal microbial metabolites play an important regulatory role in intestinal I/R injury [6].…”
Section: Introductionmentioning
confidence: 74%
“…There are direct or indirect interactions between them, and they form a complex interaction network with the host through direct contact, secreting proteins or metabolites, forming a dynamically balanced micro-ecosystem, which is closely related to human health and disease [26][27][28][29]. Existing studies have shown that intestinal microbiota is closely related to the occurrence and development of diabetes, hypertension, cardiovascular disease, tumors, etc., because of its important role in human health, it is also called the human body's forgotten organs [9,[30][31][32][33][34][35][36]. In addition, the intestinal microbiota is huge, and it contains about 100 times the number of genes in the human genome, so it is also known as the second genome of the human body [17,37,38].…”
Section: Overview Of the Intestinal Microbiotamentioning
confidence: 99%